Motor Ability of Deaf and Scientific Children - Sufitriyono Sufitriyono; Wawan Sundawan Suherman; Cerika Rismayanthi; Muhammad Akbar Syafruddin (JUARA : Jurnal Olahraga, 2023)
This research is descriptive research using a survey method with test techniques. The sample was taken purposively as a sample of 16 children with special needs who were deaf and mentally retarded. Research data collection was carried out through tests, tests for gross motor skills consisted of a test for walking on a straight line for 5 meters, a test for running to avoid 5 obstacles for a distance of 15 meters, a test for standing on one leg for 10 seconds, a test for jumping from a high beam. 15 cm, and sprint 40 meters. From the gross motor skills test of deaf and mentally retarded children in Makassar City, the results obtained were that the gross motor skills of deaf and mentally retarded children were in the medium category, namely 8 students or 88.9% and 7 students or 100% respectively. From this, researchers can conclude that the gross motor skills of deaf and mentally retarded children in Makassar City are in the medium category